Date Palm Tree (Phoenix dactylifera L.): Natural Products and Therapeutic Options - Al-Alawi, Reem A.; Al-Mashiqri, Jawhara H.; Al-Nadabi, Jawaher S. M.; Al-Shihi, Badria I.; Baqi, Younis (Frontiers in Plant Science, 2017)
Many plants, including some of the commonly consumed herbs and spices in our daily food, can be safely and effectively used to prevent and/or treat some health concerns. For example, caffeine the active ingredient found in coffee beans (Coffea), shows biological activity in the treatment of the central nervous system (CNS) disorders, indole-3-carbinol and 3,3'-diindolylmethane are both broccoli (Brassica oleracea) derived phytochemicals with potential anti-cancer activity, and resveratrol, isolated from grape (Vitis vinifera), is reported to extend lifespan and provide cardio-neuro-protective, anti-diabetic, and anti-cancer effects. Date palm fruits possess high nutritional and therapeutic value with significant antioxidant, antibacterial, antifungal and anti-proliferative properties. This review focuses on the date fruits extracts and their benefits in individual health promoting conditions and highlights their application as useful to the nutraceutical and pharmaceutical industries in the development of natural compound-based products.